The Impact of the Optical Properties and Respiration of Algal Cells with Truncated Antennae on Biomass Production Under Simulated Outdoor Conditions - Schramm, Anja; Jakob, Torsten; Wilhelm, Christian (Current Biotechnology, 2016)
Background: Previous studies have shown the positive effect of genetically induced antenna truncation on the photosynthetic performance of mutant strains (tla). From the increase of maximum photosynthesis rates per unit chlorophyll under saturating irradiance, it has been concluded that photobioreactors with tla mutants could be operated at higher cell numbers and should show increased biomass production under high irradiance. Objective: The potential of three wild type (WT) strains and one tla mutant of Chlamydomonas reinhardtii to adjust cellular Chlorophyll content (Chlcell) in response to different light conditions and its consequences for the cell physiology was investigated. Results: Under high growth irradiance, some WT strains can achieve a comparable level of antenna reduction as observed in the tla mutant. Respiration and maximum photosynthesis rate showed an inverse correlation with Chlcell independently of whether antenna size reduction was achieved by light adaptation or by genetic transformation. Thus, under diurnal light conditions increased respiratory losses compensate for increased photosynthesis rates and exert negative impact on biomass production. The reduction of Chlcell inevitably resulted in an increase of the absorption efficiency of Chl. This implies that cell number and transparency in a bioreactor cannot be increased to a similar extent as expected from Chlcell reduction. Conclusion: Under natural light conditions, the negative impact of increased respiration and absorptivity of antenna truncated cells has to be taken into account to judge the biomass production potential of antenna truncated alga strains. A further reduction of antenna size beyond the current degree could even decrease biomass productivity. Alternative approaches to increase biomass productivity of photobioreactors are suggested. Keywords: antenna truncation, tla mutants, biomass production, Chlamydomonas reinhardtii
Keywords: biomass production